Developement of perception of coarticulation - Bhuvaneshwari C.S (Journal of All India Institute of Speech and Hearing, 1970)
The term coarticulation denotes an overlap in the production of gestures for successive segments of an utterance (MacNeilage '80). In the past, studieshave been conducted on coarticulation and there has been some light thrown on the development of coarticulation in children. However, the research is notvery conclusive and much remains to be done in this regard. The present study was an attempt to investigate and gain insight into the development ofthe perception of coarticulation in Kannada speaking children from 4-7 years of age.